The future : [large type] a novel - Alderman, Naomi (Thorndike Press large print high octane., 2023)
"When Martha Einkorn fled her father's compound, she never expected to find herself working for a powerful social media mogul. Now, she's surrounded by mega-rich companies spouting technological prophecy. Across the world, in a mall in Singapore, Lai Zhen, an internet-famous survivalist, flees from an assassin. Suddenly, a piece of software appears on her phone telling her exactly how to escape. Martha and Zhen's worlds are about to collide. While a few billionaires assured of their own safety lead the world to destruction, Martha's relentless drive and Zhen's insatiable curiosity could lead to something beautiful or the cataclysmic end of civilization"--